Nilai-Nilai Pendidikan Karakter Dalam Novel Rasa Karya Tere Liye Dan Relevansinya Terhadap Pembelajaran Sastra Di SMP - Krisna Rawanti; Misriani Misriani; Achmad Wahidy (Departement of Mathematics Education, 2023)
Chaeacter education is a human activity that trains abilities with educational actions in order to lead to a better life for the next generatuon. The objektive of this research is to describe and find out the value of character education contained in Tere Liye’s novel Rasa. Character education in this study can teach how a person must instill good attitudes or character from an early age so that human beings with good character are formed so that they can distinguish between what is good and what is bad so that differences between individuals are formed. In thid study the method used is descriptive with a qualitatuve research form. The focus in this study is the value of character education contained in the Tere Liye’s novel Rasa, while the subfocus is examining the value of character education contained in the Tere Liye’s novel Rasa. Data analysis used documentation techniques which then conclusions can be drawn from this analysis. The result of this study are 9 values of character education from the novel Rasa by Tere Liye which include: (1) relihious, (2) tolerance, (3) discipline, (4) hard work, (5) independent, (6) creative, (7) curiosity, (8) fond of reading, (9) friendly/communicative.